Rate of Schneiderian First Rank Symptoms among Newly Diagnosed Schizophrenic Patients - Al-Yasiri, Abdul-Rasoul; Rahim, Twana A. (AL-Kindy College Medical Journal, 2008)
Background: Schneiderian first rank symptoms areconsidered highly valuable in the diagnosis ofschneideria.They are more evident in the acute phase of thedisorder and fading gradually with time. Many studieshave shown that the rate of these symptoms arevariable in different countries and are colored bycultural beliefs and values.Objectives: To find out the rate of Schneiderian firstrank symptoms among newly diagnosed schizophrenicpatients, to assess which symptom(s) mightpredominate in those patients, and to find out if thereis/are any correlation(s) between the occurrence ofthese symptoms and the sex of the patients.Methods: Out of twenty-four patients with no pastpsychiatric history and whom were diagnosed asSchizophrenia for their first time depending onDiagnostic and Statistical Manual-4th Edition-TextRevised criteria for diagnosis were evaluated for thepresence of Schneiderian First Rank Symptoms byusing a semi-structured interview schedule.Results: Out of twenty -three patients (54.7%) hadpresent with one or more Schneiderian First RankSymptoms.' Third person Hallucinatory Voices","running Commentary Hallucinatory Voices', and "Somatic Passivity" were present more frequently thanother symptoms.The study revealed no sex differences in regard of theoccurrences of the Schneiderian (FRS). More than 82%of those who had the symptoms showed more than onesymptom.Conclusions: Many factors influence the presence orabsence of Schneiderian First Rank Symptoms amongschizophrenic patients including the criteria selectedfor the diagnosis of the disorder, the tools adopted forthe detection of these symptoms, the duration of theillness, and probably patient's cultural background.Although there are individual differences of First RankSymptoms among different cultures, still we expectcertain symptoms to be present more than others. Theinfluence of cultural factors in altering the basicsymptoms of psychiatric illnesses is of greatimportance